2020
DOI: 10.1111/jipb.12925
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose‐6‐phosphate phosphatase E modulates ABA‐controlled root growth and stomatal movement in Arabidopsis

Abstract: Trehalose plays important roles in plant growth and stress responses and is synthesized from trehalose-6-phosphate by trehalose-6-phosphate phosphatase (TPP). Here, we show that trehalose and abscisic acid (ABA) have synergistic effects on root growth and stomatal closure. The Arabidopsis thaliana genome contains ten genes encoding TPPs and the expression level of one, TPPE, and trehalose contents increased in response to ABA. In the presence of ABA, the ABA-responsive transcription factor ABA RESPONSE ELEMENT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 54 publications
0
50
0
Order By: Relevance
“…T6P, an highly soluble and low molecular weight compound, works as osmoprotectant by enhancing the resistance against salt stress 52 . Moreover, T6PP expression and trehalose content are increased in response to ABA and the synergistic action between the disaccharide and ABA also leads to a positive effect on root elongation in Arabidopsis 53 . ABA 8′-hydrolase, is a cytochrome P450 enzyme, involved in ABA catabolism, and importantly in maintaining the hormone balance 54 .…”
Section: Resultsmentioning
confidence: 99%
“…T6P, an highly soluble and low molecular weight compound, works as osmoprotectant by enhancing the resistance against salt stress 52 . Moreover, T6PP expression and trehalose content are increased in response to ABA and the synergistic action between the disaccharide and ABA also leads to a positive effect on root elongation in Arabidopsis 53 . ABA 8′-hydrolase, is a cytochrome P450 enzyme, involved in ABA catabolism, and importantly in maintaining the hormone balance 54 .…”
Section: Resultsmentioning
confidence: 99%
“…Measurements of stomatal aperture were performed as described previously (Wang et al ., 2020). Briefly, epidermal peels were stripped from leaves of 4‐wk‐old plants grown in a glasshouse under the conditions described in the previous paragraph, and incubated in the resting buffer for 2.5 h under a light intensity of 150 μmol m −2 s −1 or in the dark with or without 1 μM ABA.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that almost all factors of stomatal closure can induce H 2 O 2 accumulation, and the H 2 O 2 level in guard cells directly affects the stomatal closure process (Mittler and Blumwald 2015;Singh et al 2017;Qi et al 2018;Islam et al 2019). Wang et al (2020) reported that TPPE, Arabidopsis trehalose-6-phosphate phosphatase E, participates in ABAinduced ROS accumulation and stomatal movement regulation, and H 2 O 2 accumulation induced by ABA failed to occur in tppe mutant plants. Flavonols, a group of flavonoids, have recently been shown to be involved in guard cell H 2 O 2 accumulation and stomatal movement (An et al 2016a;Watkins et al 2017;Brunetti et al 2018Brunetti et al , 2019.…”
Section: Introductionmentioning
confidence: 99%